INVESTIGATE THE IMPACT OF STRATEGY FLEXIBILITY ON PRODUCT INNOVATION: A LITERATURE REVIEW - Saribu, Ardin Dolok (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2020)
In the current era of globalization, companies are required to be responsive to technological developments and economic progress in order to be able to face increasingly fierce competition. One way that can be done to deal with this problem is to innovate on products to produce products with superior quality in an effort to manage the business. This success can be achieved by implementing strategies in product innovation activities. By innovating products, the company's chances of getting new customers will be even greater and sales will increase